2012
DOI: 10.33961/jecst.2012.3.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Ranitidine and Metronidazole at Poly(thionine) Modified Anodized Glassy Carbon Electrode

Abstract: A simple and sensitive electrochemical sensor for simultaneous and quantitative detection of ranitidine (RT) and metronidazole (MT) was developed, based on a poly(thionine)-modified anodized glassy carbon electrode (PTH/GCE). The modified electrode showed the excellent electrocatalytic activity towards the reduction of both RT and MT in 0.1 M phosphate buffer solution (PBS, pH 7.0). The peak-to-peak separations (∆E p) for the simultaneous detection of RT and MT between the two reduction waves in CV and DPV wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…An analytical comparison was performed in Table 6 to show the advanced sensitivity and efficiency of the suggested potentiometric modified sensors for the determination of RNT with other previously reported analytical techniques [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The comparative results showed that the suggested modified sensors using metal oxide nanoparticles exhibited higher sensitivity over a wide concentration range than those reported by the previously developed sensors.…”
Section: Resultsmentioning
confidence: 99%
“…An analytical comparison was performed in Table 6 to show the advanced sensitivity and efficiency of the suggested potentiometric modified sensors for the determination of RNT with other previously reported analytical techniques [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The comparative results showed that the suggested modified sensors using metal oxide nanoparticles exhibited higher sensitivity over a wide concentration range than those reported by the previously developed sensors.…”
Section: Resultsmentioning
confidence: 99%
“…boron-doped diamond(BDD) electrode SWASV À0.977 0.1-4.2 0.065 [39] PTH/GCE DPV À0.550 35-500 0.96 [40] Cu-poly (Cys)/GCE LSV À0.721 0.5-400 0.37 [41] Poly(chromotrope2B)/GCE DPV À0.580 10-400 0.33 [42] CPE a-CD DPV -0.5-103.0 0.28 [43] AgNPs/SF-GR/GCE DPSV -0.1-20.0 0.05 [44] Ni/Fe-layered double hydroxides /GCE CV À0.697 5-1595 58 [45] MWCNTs/CTSÀNi/GCE DPV À0.614 0.1-150 0.025 [37] AgNPs/IL/CA SPCE DPV -3.1-310 310-1300 0.4 [46] Polydopamine/MWCNs-COOHnanocomposites/GCE DPV À0.678 5-300 300-800 800-5000 0.25 [47] Gr-IL/GCE DPV À0.690 0.1-25.0 0.047 [48] MIL 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 detection is 8.3 nM (S/N = 3, n = 10). Likewise, Figure 9b displays the typical DPV response of Pb(II) with increment of its concentrations (0.05 to 7.0 mM) and the linearization equation is I (mA) = 3.985c (mM) + 0.232 (R 2 = 0.9921), with a low detection limit of 6.7 nM (S/N = 3, n = 10).…”
Section: The Simultaneous Detection Of CD 2 + and Pb 2 +mentioning
confidence: 99%
“…RT and MT in pharmaceutical formulations have been determined by spectrophotometry, [10,11] chromatography, [12] atomic absorption spectrometry, [13] near‐infrared reflectance spectrometry, [14] fluorimetric method, [15] titrimetry, [16] flow‐injection chemiluminescence, [17] ion‐selective electrodes, [18] and capillary zone electrophoresis [19] . The lack of selectivity, however, limits their use in pharmacokinetic research in biological and therapeutic specimens.…”
Section: Introductionmentioning
confidence: 99%
“…MT and RT are used together in a combined therapy regimen for the treatment of acute and moderate ulcers in patients who cannot take proton pump inhibitors and 100 mg/mL and 6 mg/mL are their effective plasma concentrations, respectively. [8,9] RT and MT in pharmaceutical formulations have been determined by spectrophotometry, [10,11] chromatography, [12] atomic absorption spectrometry, [13] near-infrared reflectance spectrometry, [14] fluorimetric method, [15] titrimetry, [16] flow-injection chemiluminescence, [17] ion-selective electrodes, [18] and capillary zone electrophoresis. [19] The lack of selectivity, however, limits their use in pharmacokinetic research in biological and therapeutic specimens.…”
Section: Introductionmentioning
confidence: 99%